Gender-Specific Differences in the Association of Adiponectin Gene Polymorphisms with Body Mass Index (The Review of Diabetic Studies, 2023)
OBJECTIVE: Adiponectin gene polymorphisms are associated with obesity, metabolic syndrome and type 2 diabetes (T2D). The study evaluated possible associations of +45T/G and -11391G/A adiponectin gene polymorphisms with body mass index (BMI), waist circumferences (WC), and blood pressure in diabetic and non-diabetic Iranians. METHODS: This cross-sectional study involved two groups of subjects: 243 diabetic patients and 173 non-diabetic subjects recruited from Rafsanjan city in the south-east of Iran. RESULTS: No significant association was found between +45T/G and - 11391G/A adiponectin gene polymorphisms and systolic or diastolic blood pressure. However, male carriers of the TT genotype of +45T/G had a significantly higher mean BMI than male GG homozygotes (p = 0.018). Also, male carriers of the GG genotype of -11391G/A had significantly higher mean BMI than male GA or AA homozygotes (p = 0.041). Female carriers of the GG genotype of -11391G/A had significantly higher mean WC than female GA or AA homozygotes (p = 0.038). CONCLUSIONS: We observed a significantly higher BMI in women, and GA or AA carriers of - 11391G/A polymorphism. Also, there was a significantly lower WC in females and GG carriers of +45T/G. These results point to a gender-specific impact of the studied genotypes on BMI and WC.